2022
DOI: 10.1021/acs.analchem.1c03792
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Site Fluorescent Sensor as a Multiple Logic System for Studying the Dichotomous Function of Sulfur Dioxide under Oxidative Stress Induced by Peroxynitrite

Abstract: Intracellular reactive oxygen species and reactive sulfur play a vital role in regulating redox homeostasis and maintaining cell functions. Sulfur dioxide (SO2) has emerged as an important gas signal molecule recently, which is not only a potential reducing agent but also a potential inductor of oxidative stress in organisms. Due to high reactivity, peroxynitrite (ONOO–) could act on many biomolecules, such as proteins, lipids, and nucleic acids, and cause irreversible damage, eventually leading to cell apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…Experimental cells were pretreated with lipopolusaccharide (LPS), in which ONOO − was up-regulated accurately. 23,54 In contrast, the control group cells were pretreated with the ONOO − scavenger TEMPO (superoxide scavenger) 55 and amino guanidine (AG, nitric oxide synthase inhibitor). 56 SQDC@BSA emitted strong red fluorescence in experimental group cells but showed very weak fluorescence in control group cells (Figures S15 and 16).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Experimental cells were pretreated with lipopolusaccharide (LPS), in which ONOO − was up-regulated accurately. 23,54 In contrast, the control group cells were pretreated with the ONOO − scavenger TEMPO (superoxide scavenger) 55 and amino guanidine (AG, nitric oxide synthase inhibitor). 56 SQDC@BSA emitted strong red fluorescence in experimental group cells but showed very weak fluorescence in control group cells (Figures S15 and 16).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A strength of molecular logic devices is their operation in nanometric biocompatible spaces such as membranes, [93] cell surfaces [94] and inside living cells. [71,[95][96][97] Semiconductor logic devices [11] cannot function sustainably in these environments. Although the logical complexity of small-molecule systems is small, it can be sufficient to answer important questions in the cellular milieu.…”
Section: Discussionmentioning
confidence: 99%
“…Although the logical complexity of small-molecule systems is small, it can be sufficient to answer important questions in the cellular milieu. Currently available examples [71,[95][96][97] show the way to go.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, when MMP was decreased due to mitochondrial damage, TC-2 could escape from mitochondria to the nucleus with a prolonged fluorescence lifetime, which could be monitored efficiently by confocal laser scanning microscopy (CLSM) and fluorescence lifetime imaging microscopy (FLIM). Moreover, it was demonstrated that the concentration of SO 2 as an antioxidant increased when MMP decreased due to oxidative stress. , This work proposed a new strategy to fulfill the dual-detection of mitochondrial SO 2 and MMP, which would provide valuable insights for the study of mitochondrial-related diseases among various physiological and pathological processes.…”
mentioning
confidence: 97%
“…Moreover, it was demonstrated that the concentration of SO 2 as an antioxidant increased when MMP decreased due to oxidative stress. 35,36 This work proposed a new strategy to fulfill the dual-detection of mitochondrial SO 2 and MMP, which would provide valuable insights for the study of mitochondrial-related diseases among various physiological and pathological processes.…”
mentioning
confidence: 99%